The rise and fall of South Korea's new community movement - Ahn, Byong Man; Boyer, William W. (1989)
South Korea's cooperative self-help community development program, so successful in the early 1970s in effecting visual village improvements, was expanded nationwide in the military sites. Participating organizations proliferated and the whole populace became the target for self-sacrificing involvement and indoctrination. But the 1980s witnessed destabilization and ultimate demise of the program. This study analyzes the rise and fall of the movement, how it lost its public appeal, and how it became discredited and stigmatized. Overcentralization, overexpansion, authoritarianism, mismanagement and corruption brought it to a virtual halt, with the imprisonment of its leaders and a national campaign for "democratization." The authors draw lessons from this experience and suggest directions for the future.
Keywords: Community development -- Korea (South); South Korea -- Politics and government